Local Currency Bond Markets Law Reform : A Methodology for Emerging Markets and Developing Economies - Bossu, Wouter (IMF Working Papers; Working Paper ;, 2020)
Recent financial crises including the ongoing one caused by the COVID-19 pandemic have consistently drawn attention to the need to strengthen the quality of public debt management in emerging markets and developing countries. Deeper and more efficient domestic government debt markets-being, a key segment of the LCBM for many emerging markets and developing economies-play a key role in reducing financial vulnerability to shocks and enable governments to finance critical economic and fiscal policy measures in response to them. Policymakers and international organizations have long recognized that developing and strengthening LCBMs is a key policy prescription to sound public debt management. Robust legal and regulatory frameworks are recognized as being critical building blocks for the structure, development and functioning of LCBMs. This Working Paper seeks to outline a strategically anchored methodology that can be applied to design, build and implement the legal and tax foundations for the development of LCBMs that would adequately address common challenges and impediments.